Functional physical properties of selected asian yam (Dioscorea spp.) flour (2001)
Flours from a total of 15 genotypes of dioscorea alata, D. esculenta, D. hispida, D. pentaphylla and D. rotunda were evaluated to identify variation in starch-related functional properties affecting their quality for use in food processing. Significant differences were obtained among and within species for these properties. Low to high apparent amylose contents (AAC) were found which were correlated to swelling volume (FSV), to gelatinization and pasting properties, and to get textural parameters. Very low amylose flours (3.8%-7.4%) such as D. esculenta showed high FSV, lower gelatinization temperatures (GT), low paste viscosities and high breakdown, and soft, sticky, and cohesive gel textures. These types of properties are potential for frozen products, sauces, desserts, thickeners, binders, and other similar applications. D. rotundata flours gave slightly higher AAC and GT compared to D. esculenta, but moderately high and variable paste viscosities and firm, non-sticky gel textures. D. hispida flour had low AAC and GT but extremely high paste viscosity, and low paste stability. Flours from wild and cultivated genotypes of D. pentaphylla and D. alata showed a range of properties with potential for use in noodle-making, bakery products, and for industrial uses requiring high viscosity. Genotypes BSUP 115 and BSUO 126 (D. pentaphylla) showed strong resistance to mechanical disintegration (shear-thinning). The purple, highly genotype LA 077 of D. alata gave the highest paste viscosity values and setback ratios. This was followed by the processing type BSUA 093. BSUA 102 and wild staple substitute BSUA 101; the Puerto Rican IA 227 and the Chi8nese IA 401 Flours gave extremely low paste viscosities, and somewhat firm, non-sticky gel textures.
Keywords: Yam flour; Yams